Princípio de Arquimedes: uma abordagem multicontextual na formação docente - Oliveira, Mara Cristina Júlio de (2022)
The introduction of discussions on the Nature of Science for the scientific literacy of Basic Education students has been a recurrent request in educational legislation, and the use of the History of Science has been pointed out as one of the possibilities for this insertion. However, it is customary to observe a marked deficiency in didacticpedagogical materials, which do not meet the legal requirements related to the History of Science and the Nature of Science and present an outdated historiography. The teacher, whose training is generally deficient in these aspects, is not prepared to identify these gaps and act in a way to alleviate them. Considering these two aspects, we developed an educational product for the initial and continued training of Basic Education Physics teachers. It is a support material for a teacher training course that proposes a multicontextual approach to Archimedes' Principle, covering scientific, meta-scientific and pedagogical aspects. The proposed material contemplates several objectives. It seeks to insert teachers in training in activities to reflect on aspects of the historical construction of Archimedes' Principle from primary and secondary sources in the History of Science. More particularly, in historical terms, its clipping is the episode involving Archimedes and the crown of King Hieron of Siracura. It seeks to bring together undergraduates and professors in the field of reading accessible academic materials on specific physical content and of interest to the Teaching of Physics. It also proposes reflection on the Nature of Science theme and raising awareness of the importance of didactic use of the History of Science through the study of excerpts from educational legislation and public notices from the National Textbook Program. It seeks to sensitize this audience about the need to evaluate allusions to historical elements, narratives and possible initiatives for the didactic transposition of the History of Science present in textbooks. Considering these objectives, the application of the educational product was carried out in an extension course and had as target audience active and in-training teachers from different regions of the country, who accompanied him remotely. We discussed the results obtained in the application, and, as a result of what was noticed, we presented suggestions to possible interested parties in the use of the educational product.